2005
DOI: 10.1590/s1415-52732005000100007
|View full text |Cite
|
Sign up to set email alerts
|

Obtenção e caracterização química e nutricional de diferentes concentrados de caseína

Abstract: ObjetivoO objetivo deste trabalho foi avaliar a composição centesimal, o perfil de aminoácidos e as características nutricionais de três concentrados de caseína, obtidos do leite bovino por diferentes processos. MétodosOs concentrados de caseína foram analisados pelos seguintes processos: uma caseína comercial, obtida por precipitação ácida seguida de neutralização; caseína obtida pela coagulação enzimática; caseína micelar obtida, respectivamente, pelos processos de microfiltração e diafiltração em membrana. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Inhibition assays revealed that BlL was partially inhibited by fetal bovine serum and casein, but not by fetuin and asialofetuin (Table 2). Casein is a protein with a small carbohydrate fraction and contains phosphorus in its structure (Roman and Sgarbieri, 2005). Two N-glycosidic carbohydrate complex-types rich in galactose are present in the structure of α-fetoprotein, a protein found in fetal bovine serum (Krusius and Ruoslahti, 1982); the presence of galactose may be responsible for the inhibition of BlL in the presence of fetal bovine serum.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition assays revealed that BlL was partially inhibited by fetal bovine serum and casein, but not by fetuin and asialofetuin (Table 2). Casein is a protein with a small carbohydrate fraction and contains phosphorus in its structure (Roman and Sgarbieri, 2005). Two N-glycosidic carbohydrate complex-types rich in galactose are present in the structure of α-fetoprotein, a protein found in fetal bovine serum (Krusius and Ruoslahti, 1982); the presence of galactose may be responsible for the inhibition of BlL in the presence of fetal bovine serum.…”
Section: Resultsmentioning
confidence: 99%
“…A digestibilidade verdadeira encontrada para a rã sem osso foi superior que todas as demais estudadas, porém não diferiu (p>0,05) dos valores encontrados para a digestibilidade da caseína (93,33%), CMS (92,57%), carne bovina (92,38%) e rã com osso (91,01%). ROMAN & SGARBIERI [26] se depararam com digestibilidade verdadeira de 93,78% para caseína comercial, bem próximo ao encontrado no presente trabalho.…”
Section: -Avaliação Biológica Das Proteínasunclassified
“…The results of the centesimal composition of the pequi seed and the defatted pequi seed flour used in this study are shown in Table 2. The concentration of lipids found in the pequi seed was 55.4% and the protein content was 25.3%. In the defatted flour, the lipids represented only 3.0% of the sample and the proteins, 65.5%.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 92%
“…The PER of the group fed with the casein diet showed to be significantly superior to the other groups, which may be justified by the higher food and protein intake and, consequently, higher weight gain by this group. Because it is an animal protein, casein has all the necessary essential amino acids in adequate amounts for the growth and maintenance of the organism [55].…”
Section: Designmentioning
confidence: 99%